FOSTERING LEARNER AUTONOMY THROUGH WEB-BASED LEARNING - Sri Suryatiningsih (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
One of the requirements for nowadays adult learning is to be learner autonomy. Learner autonomy is the ability to take charge of one’s own learning. Learner autonomy can be nurtured through web-based learning. Web-based learning is a platform that can be used for individual learning needs anytime anywhere they want, in accordance, the learner is often learning without interaction with other people directly. There are some problems in implementing web-based learning in Indonesia. Students felt dissatisfied with the current system and the lack of teacher’s feedback and scaffolding. This study tried to investigate what is the learner’s perception of improving learner autonomy using web-based learning. This study is a case study. The instrument used are questionnaire and interview. This study uses analytical analysis. There are some drawbacks that demotivate the students such as the poor variety of media, the lack of teacher’s scaffolding and confirmation. Web-based learning is able to help students in sending their homework, participate in online discussion, increase their critical thinking, get immediate feedback and share ideas. For recommendation, SPOT UPI needs to be developed well to promote learner autonomy.